Entangled histories of place and reconfigurations of diasporic home: Al‐Andalus history and the Moroccan diaspora in Granada, Spain. Issue 3 (19th November 2021) - Finlay, Robin
Abstract: In this paper, I contribute to scholarship on diasporic geographies of home and develop ideas around "diaspora transregions" and "diaspora cities." To do this, I examine Moroccan diaspora formations in the city of Granada in the south of Spain. I utilise the spatiality and history of Granada to reveal complex interpretations of diasporic home. In particular, I examine how the Muslim history of Al‐Andalus – which is intimately embedded in the urban landscape of Granada and also entangled into the history of the wider region – impacts on Moroccan diaspora consciousness. This involves examining how histories and geographies of Al‐Andalus are interpreted and experienced by those in the Moroccan diaspora, which in this analysis is a diasporic population primarily from northern Morocco. I analyse four intersecting impacts of history and place, including nostalgia and imagined geographies, religious and genealogical links to Granada and the wider region, identification with culture and the built environment, and finally the ambivalence of history on belonging. What this examination reveals is that the history of Al‐Andalus and an identification with historical circular migrations between northern Morocco and southern Spain can engender a sense of being part of multiple diasporic journeys and settlements, and subsequently a 'homing desire' to multiple spaces. A key contribution here is the illustration of how entangled urban and regional histories can reconfigure more normative notions of the diaspora condition. Diasporic connections to deep histories of place and migration can rework senses of home and refute notions of a linear homing desire to a singular nation‐state. This demonstrates that diasporic belongings are not always limited to the parameters of the nation, but rather are informed by the intersections of urban and regional cultures, religions, and histories. Abstract : In this paper, I examine Moroccan diaspora formations in the city of Granada in the south of Spain. I utilise the spatiality and history of Granada to reveal complex interpretations of diasporic home. In particular, I examine how the Muslim history of Al‐Andalus – which is intimately embedded in the urban landscape of Granada and also entangled into the history of the wider region – impacts on Moroccan diaspora consciousness and senses of home.